2023
DOI: 10.21203/rs.3.rs-2405953/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploration of symptom clusters during hemodialysis and symptom network analysis of older maintenance hemodialysis patients: a cross-sectional study

Abstract: Background Symptom networks can provide empirical evidence for the development of personalized and precise symptom management strategies. However, few studies have established networks of symptoms experienced by older patients on maintenance hemodialysis. To examine the type of symptom clusters of older maintenance hemodialysis patients during dialysis and construct a symptom network to understand the symptom characteristics of this population. Methods The modified Dialysis Symptom Index was used for a cross… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Based on our ndings and previous studies, we concluded that psychological symptoms, including feeling sad, worrying, feeling nervous, panic, depression, and anxiety, were central symptoms for patients, affecting other symptoms negatively. 17,36,37 These ndings imply that clinical staff and researchers should understand the psychological states and cognitive processes of AML patients receiving chemotherapy. Additionally, it was reported that mindfulness-based interventions, meaningenhancing interventions, dignity therapy, life review, and aromatherapy could relieve the psychological burden of patients and promote positive moods, which may be essential for the emotional management of adult AML patients 34,38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our ndings and previous studies, we concluded that psychological symptoms, including feeling sad, worrying, feeling nervous, panic, depression, and anxiety, were central symptoms for patients, affecting other symptoms negatively. 17,36,37 These ndings imply that clinical staff and researchers should understand the psychological states and cognitive processes of AML patients receiving chemotherapy. Additionally, it was reported that mindfulness-based interventions, meaningenhancing interventions, dignity therapy, life review, and aromatherapy could relieve the psychological burden of patients and promote positive moods, which may be essential for the emotional management of adult AML patients 34,38 .…”
Section: Discussionmentioning
confidence: 99%
“…An NA can provide supplementary data for a clinical paradigm, including strength, closeness, and betweenness data, which may contribute to developing more specialized treatments and pertinent management 14 . To date, NA studies have been conducted in patients with chronic diseases, including cancer, mental disorders, hemodialysis, and HIV [15][16][17][18] . For example, a historical cross-sectional study revealed that worrying and feeling irritable were the central symptoms across three centrality indices in 469 children with AL during chemotherapy 19 .…”
Section: Introductionmentioning
confidence: 99%